Web-Based Tsunami Early Warning System - Daniel Siahaan; Royke Wenas; Amien Widodo; Umi Yuhana (IPTEK The Journal for Technology and Science, 2013)
Tsunami is a serious threat to the island nation such as Indonesia. The tsunami disasters that were occurred in some parts of Indonesia have immerged the need for tsunami early warning system that is reliable and can be applied to the Indonesian archipelago. North Sulawesi is one of the areas prone to tsunamis since this area lies in the path called the ring of fire's. This article describes a tsunami simulation application for the north coast of North Sulawesi. Web-based applications were built so that they can be monitored online from anywhere and at anytime. This system reads the real-time seismic data that affect the North Sulawesi region from a number of sources. Dynamic and static data that are received are processed using data mining method to predict the chances of a tsunami, while flood flooding algorithm is used to visualize the map of affected areas of North Sulawesi. The resulting information is available in detail in the form of web pages and also through short message to the relevant authorities handling of the tsunami disaster in order for them to act in accordance with applicable standard operating procedures. With this application, the public can obtain information that is more accurate. Relevant authorities can conduct tsunami disaster mitigation measures more effectively.